Formulation and Evaluation of Niosomes of Clopidogrel for the Treatment of Peripheral Artery Disease - Vishwakarma, Vinamrata; Joshi, Garvita; Chourasiya, Anjali; Jain, Vikas (Journal of Neonatal Surgery, 2025)
Peripheral Artery Disease (PAD) is a progressive vascular condition that significantly elevates the risk of thrombotic events. Clopidogrel, a widely used antiplatelet agent, is limited by systemic side effects and poor bioavailability. This study focuses on the formulation and evaluation of Clopidogrel-loaded niosomes to enhance therapeutic efficacy through improved encapsulation, stability, and controlled release. Among the developed formulations, the optimized niosomal formulation (F2) demonstrated high drug entrapment efficiency (94.60 ± 16.90% initially and 89.47 ± 2.50% after 3 months), indicating excellent drug loading capability. In vitro drug release studies revealed a sustained and controlled release profile, with F2 releasing 3.22 ± 0.38 mg (approximately 39% of the total drug load) of Clopidogrel over 24 hours, outperforming F3, which released only 2.50 ± 0.64 mg (15%). Stability studies confirmed the physical robustness of F2, with no significant change (p > 0.05) in vesicle size or entrapment efficiency over a 3-month period at 4 °C, unlike F1 and F3, which exhibited significant increases in particle size. The nanoscale vesicle size of F2, maintained through a balanced 1:1 cholesterol-to-surfactant ratio, contributed to its enhanced stability and drug release properties. The optimized surfactant composition improved vesicle rigidity and integrity, essential for prolonged release and targeted delivery. Importantly, the encapsulation of Clopidogrel in niosomes may reduce systemic side effects such as gastrointestinal irritation, offering a promising alternative to conventional formulations for the effective management of PAD.